Pharmacokinetic–pharmacodynamic studies of the 11β‐hydroxysteroid dehydrogenase type 1 inhibitor MK‐0916 in healthy subjects. (December 2013) - Wright, D. Hamish; Stone, Julie A.; Crumley, Tami M.; Wenning, Larissa; Zheng, Wei; Yan, Kerri; Yang, Amy Yifan; Sun, Li; Cilissen, Caroline; Ramael, Steven; Hermanowski‐Vosatka, Anne; Langdon, Ronald B.; et al.
<x xml:space="preserve">Abstract</x> Aims To characterize pharmacokinetic parameters of MK‐0916 and its safety and tolerability in lean, healthy male subjects following single and multiple oral doses. To assess (by stable‐isotope labelling) the in vivo inhibition of cortisone‐to‐cortisol conversion following oral MK‐0916. Methods Data are presented from two randomized, controlled, double‐blind, rising‐dose phase I studies. In the first study, subjects received single oral doses of 0.4–100 mg MK‐0916 (n = 16). In the second study, subjects received 0.2–225 mg MK‐0916 followed by daily doses of 0.2–100 mg for 13 days beginning on day 2 or day 15 (n = 80). Plasma and urine drug concentrations were measured for pharmacokinetic analysis. For pharmacodynamic analysis, concentrations of plasma [13C4]cortisol were measured by high‐pressure liquid chromatography and tandem mass spectrometry following a single oral dose of 5 mg [13C4]cortisone. Results Doses ≥3 mg were rapidly absorbed (time at which maximal concentration was achieved in plasma, 1.1–1.8 h). Exposure (measured as the area under the concentration–time curve from 0 to 168 h) increased approximately in proportion to dose. Values for the maximal plasma concentration and the plasma concentration at 24 h increased in excess of dose proportionality at doses <6 mg and roughly in proportion to dose at doses >6 mg. In subjects dosed with 6 mg MK‐0916 once daily for 14 days, the mean trough plasma concentration was 240 nm and in vivo cortisone‐to‐cortisol conversion was inhibited by 84%. The relationship between plasma MK‐0916 and hepatic 11β‐hydroxysteroid dehydrogenase type 1 inhibition was well represented by a simple Emax model with an IC50 of 70.4 nm. Exposure to MK‐0916 was generally well tolerated. Conclusions These findings indicate that 11β‐hydroxysteroid dehydrogenase type 1 is effectively inhibited in human subjects by doses of MK‐0916 that are well tolerated.